1986
DOI: 10.1007/bf00199798
|View full text |Cite
|
Sign up to set email alerts
|

Arrens Zn (Pb), Ba Devonian deposit, Pyrénées, France: an exhalative-sedimentary-type deposit similar to Meggen

Abstract: Abstract. The Perrefitte anticlinorium district in the Paleozo[c province of the Pyrenees contains abundant mineral occurrences, prospects, and old mines in the upper volcano-sedimentary layer of the Ordovician and Devonian sediments which have been metamorphosed in the greenschist to amphibolite facies. Although of different lithologic environments, the mineralization shows, as everywhere in the Pyrenees, many common characteristics. However, the Arrens deposit outcropping over 5 km on both limbs of a synclin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…SEDEX deposits are sedimentary controlled and syn-to diagenetic, and sulfides in them are laminated and included into the bedding [2]. In our study area, Pyrenean Pb-Zn mineralizations have been previously described as SEDEX by many authors [24,[28][29][30]75,76]. The origin of several world-class Pb-Zn deposits is debated as well.…”
Section: Is Pb-zn Deposits Emplacement Sedimentary-or Structurally-comentioning
confidence: 99%
“…SEDEX deposits are sedimentary controlled and syn-to diagenetic, and sulfides in them are laminated and included into the bedding [2]. In our study area, Pyrenean Pb-Zn mineralizations have been previously described as SEDEX by many authors [24,[28][29][30]75,76]. The origin of several world-class Pb-Zn deposits is debated as well.…”
Section: Is Pb-zn Deposits Emplacement Sedimentary-or Structurally-comentioning
confidence: 99%
“…More usually, whenever Ge is present, it is enriched in the sphalerite (ZnS) lattice rather than as independent Ge-minerals (Reyx, 1973;Johan et al, 1983;Laforet et al, 1981;Bernstein, 1985;Cook et al, 2009Cook et al, , 2015. These Geminerals may be brunogeierite (GeFe 2 O 4 ), argutite (GeO 2 ), Ge-chloritoid (carboirite, FeA1 2 GeO 5 (OH) 2 ), rare briartite (Cu 2 (Fe, Zn)GeS 4 ), as well as Ge-bearing lepidomelane, titanite, garnet, zoisite, chlorite, quartz, allanite, and magnetite (Laforet et al, 1981;Johan et al, 1983;Bernstein, 1985;Pouit and Bois, 1986;Johan and Oudin, 1986). The formation of Ge-minerals in the Pyrenean deposits is poorly documented until now except for Aye et al (1978) and Johan and Oudin (1986) who suggested a possible link with regional metamorphism, based on paragenetic analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Ba-feldspar rocks appear to be more common in exhalative ores; celsian forms thick monomineralic lenses, as in Aberfeldy, Scotland (Fortey and Beddoe-Stephens, 1982;Willan and Coleman, 1983). Celsian has been also reported in Arrens, Pyrenees (Pouit and Bois, 1986), and in Broken Hill, Australia (Lottemoster, 1989;Parr, 1992). In Zamora, Spain, Moro et al (2001) reported celsian lenses with hyalophane and cymrite, interlayered in apatite and massive sulfide layers.…”
Section: Introductionmentioning
confidence: 87%